Empowerment For Elderly Cadres Through Brain Exercise In Preventing Dementia In The Work Area Puskesmas Trenggalek - wulandari, dewi; Niningasih, Rahayu; Ixora, Ixora (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2023)
Trenggalek Health Center is a health center that innovates to provide services to the elderly. However, until now there has never been a Dementia examination in the elderly. Meanwhile, brain exercise is one of the activities that can prevent dementia. By training in brain exercises, the brain is invited to think actively and creatively so it is hoped that this can help strengthen brain abilities and memory. Therefore, brain exercises are good for elderly people who experience cognitive dysfunction such as dementia. The purpose of this Community Service is to provide additional knowledge about dementia and brain exercises to prevent dementia. This Community Service method is to provide counseling about dementia, measure dementia knowledge and demonstrate brain exercises. The participants were also given the opportunity to correctly demonstrate brain exercises. The results of Community Service show that there was a significant increase in knowledge before and after counseling was carried out. The application of brain gymnastics was carried out by participants in the elderly exercise group. The attendance of the participants was 100%, the participants were very enthusiastic in carrying out the brain exercise training.